Canine lung carcinoma—A descriptive review - Marcinowska, Aleksandra; Horta, Rodrigo Dos Santos; Queiroga, Felisbina; Giuliano, Antonio (Frontiers in Veterinary Science, 2025)
Primary lung cancer is a relatively uncommon tumor in dogs, accounting for about 1% of all canine malignancies. Clinical signs in affected dogs can range from being asymptomatic to exhibiting chronic cough, and in rare cases, dyspnoea. Surgical excision of the primary tumor, along with resection of the affected locoregional lymph nodes is the preferred treatment option for most cases. Although chemotherapy, targeted therapy and radiation therapy have been employed, their effectiveness remain controversial. Dogs with stage T1 tumors can experience extended survival times of up to 2 years. However, the prognosis for dogs with advanced metastatic tumors is generally very poor. This review article discusses the etiology, clinical signs, diagnosis, staging, treatment options, and prognosis of primary lung carcinoma in dogs.